Correlation between carcinoembryonic antigen and systemic immune-inflammation index with the outcomes of colorectal cancer patients who underwent radical surgery at Dr. Soetomo Surabaya during 2022-2024 - Adidharma, I Made Ary; Danardono, Edwin; Hariastawa, I G. B. Adria (Edelweiss Applied Science and Technology, 2025)
Colorectal cancer is the third most common malignancy. It occurs due to the accumulation of genetic and epigenetic changes in the cell genome that transform normal epithelial cells into adenocarcinoma. CEA (Carcinoembryonic Antigen) is a marker that is often used and is associated with carcinogenesis. The SII (Systemic Immune Inflammatory Index) is an integrated indicator based on peripheral lymphocytes, neutrophils, and platelets; it is a strong prognostic marker for hepatocellular carcinoma but has not been widely reported in cases of colorectal cancer. This research is an observational analytical study with a cohort retrospective method to link CEA and SII with the outcomes of colorectal cancer patients at RSUD Dr. Soetomo from 2022 to 2024. Data collection was obtained from medical records that met the inclusion criteria. Data analysis was carried out using SPSS software. According to the ROC curve, the optimal cutoff values for CEA and SII are 0.564 and 0.641, respectively. Based on these data, 44 samples were divided into high CEA, low CEA, high SII, and low SII groups. Statistically, there was a significant relationship between CEA and length of stay and stage; SII and length of stay also had a significant relationship (p < 0.05). However, the relationship between CEA and SII with mortality was not significant (p > 0.05). There was a significant relationship between CEA and SII values with length of stay and tumor stage. However, there was no significant relationship between CEA and SII values and mortality in colorectal cancer patients.